2016
DOI: 10.1182/blood.v128.22.611.611
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Receptor Driven MALT1 Activity Regulates MYC Signaling in Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma (MCL) is a mature B-cell lymphoma characterized by poor prognosis. Recent studies revealed the importance of constitutive B-cell receptor (BCR) signaling in maintaining survival of a subset of MCLs. MALT1 is an essential component of the CARD11-BCL10-MALT1 (CBM) complex that links BCR signaling to the nuclear factor kappa-B (NF-κB) pathway. Additionally, MALT1 functions as a protease that cleaves various substrates to promote proliferation and survival. However, its role in the molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…[206][207][208][209] MALT1 is a key mediator of the BCR signaling to NF-κB and is essential in the development of ABC-DLBCL and other lymphomas including mantle cell lymphoma, primary effusion lymphoma, and chronic lymphocytic leukemia (CLL). 136,[210][211][212][213][214] Moreover, MALT1 inhibition was shown to be effective in CLL patients, even those with mutations of BTK, PLCy, and CARD11 that cause Ibrutinib resistance. 214 Regarding TLR signaling, IRAK4 inhibitors show activity in preclinical studies in ABC-DLBCL cell lines 144 and PDXs.…”
Section: Therapeutic Targeting Of Aberrant Signal Transductionmentioning
confidence: 99%
“…[206][207][208][209] MALT1 is a key mediator of the BCR signaling to NF-κB and is essential in the development of ABC-DLBCL and other lymphomas including mantle cell lymphoma, primary effusion lymphoma, and chronic lymphocytic leukemia (CLL). 136,[210][211][212][213][214] Moreover, MALT1 inhibition was shown to be effective in CLL patients, even those with mutations of BTK, PLCy, and CARD11 that cause Ibrutinib resistance. 214 Regarding TLR signaling, IRAK4 inhibitors show activity in preclinical studies in ABC-DLBCL cell lines 144 and PDXs.…”
Section: Therapeutic Targeting Of Aberrant Signal Transductionmentioning
confidence: 99%
“…Recently, MYC protein deregulation has also been related to increased proliferation in MCL [82]. MYC stabilization is induced by MALT1 and a few aggressive MCL cases also harbour MYC rearrangement or amplification, although at low frequencies.…”
Section: Genetic Lesions In Cell Cycle Regulatorsmentioning
confidence: 99%
“…In contrast, in MALT1-inactive MCL cell lines, transduction of the BTK C481S mutant or an empty vector did not alter the cells' sensitivity to ibrutinib or to the MALT1 inhibitor. These data indicate that inhibition of MALT1 might be effective as a novel therapeutic option for patients failing ibrutinib therapy (Dai et al, 2017).…”
Section: Malt1 Inhibitionmentioning
confidence: 84%
“…CYLD cleavage may be used as a direct marker of MALT1 proteolytic activity (Staal et al, 2011). Dai et al (2017) showed that MALT1 is constitutively active in a substantial number of MCL models, and that MCLs can be divided into two distinct subgroups based on their MALT1 activation status. To investigate whether inhibition of MALT1 can overcome BTK C481S -induced ibrutinib resistance, they expressed a BTK C481S cDNA or an empty vector in five MALT1-activated and two MALT1-inactive MCL cell lines and subsequently treated these cells with ibrutinib or with a MALT1 inhibitor.…”
Section: Malt1 Inhibitionmentioning
confidence: 99%